Fulfillment of Constitutional Rights of People with Mental Disabilities in General Elections in the Batang Regency - Pratama, Agung Barok; Umam, Muhammad Rizal (Asian Journal of Law and Humanity, 2024)
Fulfillment of the political rights of persons with mental disabilities in Batang district receives serious attention because they face challenges in exercising their political rights. This includes the right to vote, to be involved in the political decision-making process and to participate actively in democratic life. The purpose of writing this thesis is to find out how the constitutional rights of persons with mental disabilities are fulfilled in general elections in Batang Regency and to find out why the fulfillment of the constitutional rights of persons with mental disabilities in general elections in Batang Regency has not been fulfilled. This research is an empirical juridical research using a qualitative approach and using primary legal materials in the form of data taken directly from the field and secondary data from relevant legal documents. The results of this study are that in the implementation of fulfilling the constitutional rights of persons with mental disabilities in general elections in Batang Regency there are still many obstacles in its implementation both from the governing regulations, law enforcement officials, and the community, therefore there are is still much to be evaluated and corrected so that fulfillment of the political rights of persons with mental disabilities can run well and smoothly.